Structural and radiation shielding properties of high-entropy rare-earth oxide-doped borosilicate glass - Guler, Omer; Yilmaz, Demet; Kanca, Muhammed Sait; Kok, Mediha; Tasgin, Yahya (Elsevier Sci Ltd, 2026)
In this study, the incorporation of a high-entropy rare-earth oxide, (GdLaEuPrDyY)2O3 (RE-HEO), into a borosilicate glass matrix was investigated with the aim of improving radiation shielding performance while preserving the structural integrity of the glass. The RE-HEO was first synthesized by high-energy mechanical alloying and then introduced into the glass system at concentrations ranging from 0 to 8 wt% using a conventional meltquenching process. The structural and microstructural properties of the prepared samples were examined using X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR), X-ray photoelectron spectroscopy (XPS), and scanning electron microscopy combined with energy-dispersive spectroscopy (SEM-EDS). The analyses confirmed that the amorphous nature of the borosilicate glass was maintained and that the rare-earth elements were homogeneously distributed within the matrix. The radiation shielding performance was evaluated experimentally using Am-241, Ba-133, and Ra-226 gamma sources, and supported by theoretical calculations of key parameters including mass attenuation coefficient (MAC), half-value layer (HVL), mean free path (MFP), effective atomic number (Zeff), exposure buildup factor (EBF), and fast neutron removal cross-section (Sigma R). The results showed that increasing RE-HEO content leads to a noticeable improvement in gamma-ray attenuation. In particular, the sample containing 8 wt% RE-HEO exhibited a MAC value of 0.131 cm2/g and an HVL of 2.03 cm at 356 keV, indicating shielding performance comparable to that of conventional lead-containing glasses. In addition, irradiation tests performed using a Co-60 gamma source revealed that the amorphous structure remains stable after exposure. Overall, the findings suggest that RE-HEO-doped borosilicate glass can be considered a promising lead-free alternative for radiation shielding applications.
Keywords: Borosilicate Glass; High-Entropy Rare-Earth Oxide; Radiation Shielding; Irradiation Stability